Maternal Smoking, Alcohol and Recreational Drug Use and the Risk of SIDS Among a US Urban Black Population - Hauck, Fern R.; Blackstone, Sarah R. (Frontiers in Pediatrics, 2022)
Background. Rates of sudden infant death syndrome (SIDS) are twice as high among Black infants compared to white infants in the US. While the contribution of sleep environment factors to this disparity is known, little is known about the risk of SIDS among Black infants in relation to maternal prenatal smoking, alcohol and drug use as well as infant smoke exposure. Objective: To assess the contribution of maternal substance use during pregnancy and the potential interactions with infant bedsharing in a high-risk, urban Black population. Methods. The Chicago Infant Mortality Study (CIMS) collected data on 195 Black infants who died of SIDS and 195 controls matched on race, age and birthweight. Risk of SIDS was calculated for maternal smoking, alcohol and drug use, adjusting for potential confounding variables and other risk factors for SIDS. Interactions between these substance use variables and bedsharing were also calculated. Results. Infants were more likely to die from SIDS if the mother smoked during pregnancy (aOR 3.90, 95% CI 1.37- 3.30) and post-pregnancy (aOR 2.49, 95% CI 1.49- 4.19). There was a dose response seen between amount smoked during pregnancy and risk of SIDS. Use of alcohol (aOR 2.89, 95% CI 1.29-6.99), cocaine (aOR 4.78, 95% CI 2.45-9.82) and marijuana (aOR 2.76, 95% CI 1.28-5.93) were associated with increased risk of SIDS. In the final, multivariable model controlling for sociodemographic factors and covariates, maternal smoking (aOR 3.03, 95% CI 1.03-8.88) and cocaine use (aOR 4.65, 95% CI 1.02-21.3) during pregnancy remained significant. There were a significant, positive interactions between bedsharing and maternal smoking during pregnancy, post pregnancy, alcohol use and cocaine use. Conclusion. Maternal use of tobacco, alcohol and cocaine during pregnancy is associated with significantly increased risk of SIDS in a Black, urban population. Reducing substance use and eliminating disparities in SIDS, SUID and infant mortality need to involve more than individual level education, but instead will require a comprehensive examination of the role of racism as well as a multi-pronged blueprint to address both maternal and infant health and wellbeing.